A ética e o financiamento das eleições no Brasil: uma análise crítica - Santos Júnior, Dirceu Fernandes dos (2015)
This work aims to discuss the relationship between ethics and the financing of elections in Brazil. In this sense, Ethics and Justice must go together, first as a minimum behavioral instruments and guiding in electoral matters, adapting to the existing social realities in our country, and increasingly to legal rules, and seek mechanisms and measures aimed at achieving social benefits. Thus, marked on Ethics, we demonstrate that the welfare state should be the promoter of Fundamental Rights and Political and Social Rights using philosophical justice approaches to the achievement of this goal, the median, proportionality actions, equality and just measure. Ethics and justice in politics, should be regarded as critical mechanisms for funding of election campaigns promoted unequal participation in relation to capital contributions exclusive source in directing political action for the coming to power. At stake is our political participation, when assessed by exclusion of equality since popular sovereignty only exists for political equality and electoral competitiveness equitably. Actions inconsistent with the ethics, not guided by social justice, dictated by donors to election campaigns with several other goals of social development as a whole, tend to political isolation and consequent failure of the electoral system. Political articulations and future benefits of certain economic groups, classes or political parties and their candidates, fighting for very different self-interest of the collective interests are promoted through mechanisms rejected by ethics, by the principles of equality and electoral legislation . This time, working on the basis of legal ethics, law and justice, we will complete the work to the promotion of positive actions, which indicate thoughts of philosophers entitled pointing out the evils of single interference of economic power in the elections